2011
DOI: 10.1200/jco.2011.35.5214
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Phase III Study of Docetaxel Plus Carboplatin With Celecoxib and Cyclooxygenase-2 Expression As a Biomarker for Patients With Advanced Non–Small-Cell Lung Cancer: The NVALT-4 Study

Abstract: In advanced NSCLC, celecoxib does not improve survival. In this study, COX-2 expression was not a prognostic biomarker and had no predictive value when celecoxib was added to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 19 publications
0
80
2
1
Order By: Relevance
“…Two recent phase III trials (Table V) (21,22) that used a design identical or similar to that of our study, failed to demonstrate any survival benefit with the addition of a COX-2 inhibitor to chemotherapy in patients with advanced NSCLC. Groen et al (21) demonstrated no statistical difference regarding survival between NSCLC patients with tumors positive and those with tumors negative for COX-2 expression, as determined by IHC.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Two recent phase III trials (Table V) (21,22) that used a design identical or similar to that of our study, failed to demonstrate any survival benefit with the addition of a COX-2 inhibitor to chemotherapy in patients with advanced NSCLC. Groen et al (21) demonstrated no statistical difference regarding survival between NSCLC patients with tumors positive and those with tumors negative for COX-2 expression, as determined by IHC.…”
Section: Discussionmentioning
confidence: 70%
“…The frequencies of grade 3/4 myopathy (2.0%) and arthralgia (0.0%) were comparable to or lower compared to those reported by several phase II trials using carboplatin plus docetaxel without a COX-2 inhibitor (3.0-4.0 and 3.0%, respectively) (15,18). Two recent phase III trials (Table V) (21,22) that used a design identical or similar to that of our study, failed to demonstrate any survival benefit with the addition of a COX-2 inhibitor to chemotherapy in patients with advanced NSCLC. Groen et al (21) demonstrated no statistical difference regarding survival between NSCLC patients with tumors positive and those with tumors negative for COX-2 expression, as determined by IHC.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1,2 Two phase III studies investigating the effect on overall survival by adding celecoxib to chemotherapy in advanced NSCLC were, however, negative. 3,4 The negative overall results do not, however, exclude a clinical role of the compound in certain subpopulations. Since one of the mechanisms involved in the antineoplastic effect of COX-2 inhibitors appears to be inhibition of angiogenesis, [5][6][7] biomarkers related to angiogenesis might be useful as predictors of a positive clinical effect on survival by celecoxib.…”
Section: Introductionmentioning
confidence: 94%